ON THE APPLICABILITY OF THE BICONJUGATE GRADIENT FFT METHOD FOR THE THIN CONDUCTING PLATE PROBLEM - TRAN, T. V. (Applied Computational Electromagnetics Society Journal (ACES), 2022)
The application of the Biconjugate Gradient FFT method to the thin conducting plate problem is investigated. Upon comparing with a Conjugate Gradient FFT method, it is found that the Biconjugate Gradient solution requires a relatively larger error tolerance to achieve a comparatively well-behaved current distribution. Coupled with the requirement of only one matrix-vector product per iteration, the computational cost of the Biconjugate Gradient method is, thus, much smaller than those previously reported in the literature. Of particular importance is the use of the incident electric field as a starting estimate to alleviate the non-convergence behaviour which is usually associated with the application of a Biconjugate Gradient approach to conducting plates at grazing angle. For other angles of incidence, it is shown that this procedure also accelerates the resulting convergence rates as compared to those obtained by simply using zero as an initial estimate. [Vol. 10, No. 1 (1995), pp 63-68]